Zarządzanie relacjami z klientem w spółkach portfelowych funduszu inwestycyjnego - Kardela, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The purpose of this paper is to present the problems related to customer relationship management in relation to the changes taking place in contemporary economic space. Thus, the analysis is based on the definition of activities undertaken in business strategies, with particular emphasis on the forms of communication aimed at activating buyers. In addition, the development of specific customer relationships that are the basis for the optimization of defined business processes in connection with the requirement for effective cost management within the scope of operating operations, has been highlihgted. That is compatible with the current market trend, which emphasizes the importance of acquiring, processing and updating information about buyer behavior and preferences. Therefore, having knowledge of the customer and managing it, nowadays determines the competitive advantage of the organization.
Keywords: transactional marketing; production concept; sales concept; marketing orientation; relation orientation; customer value orientation; integrated customer communication